Putri Cyndana dan Bayu Wulandari THE EFFECT OF PROFESIONALISM, TIME BUDGET PRESSURE AND AUDIT COMPLEXITY ON AUDIT QUALITY AT PUBLIC ACCOUNTANT OFFICES IN MEDAN - bayu Wulandari (Fakultas Ekonomi Prodi Akuntansi, 2019)
ABSTRACT The objective of the study was to examine and analyze the effects of professionalism, time budget pressure, and audit complexity on audit quality at Public Accounting Firm in Medan partially and simultaneously. The research used a qualitative research approach. The research type was a descriptive study. The nature of this study was a causal relation. The research populations were 22 Public Accounting Firm listed at IAPI. The research samples were 7 Public Accounting Firm listed at IAPI where 2 KAP were used for testing The consistency of 30 auditor validity and 5 KAP consisting of 60 auditors were used for the research samples. The measurement scale used was likert scale. The method of data analysis used in the research was multiple linear regression analysis. The result revealed that professionalism, time budget pressure, and complexity of audit affected audit quality at public accounting firm in Medan, with F-count = 11.165> F-table = 2.77 with significant level of 0,000 <0.05. Partially, professionalism with the value of T-count = 4,669> T-table = 2,00324, time budget pressure with the value of T-count = -2.026 <T-table = -2,00324, audit complexity with the value of T-count = -2,149> T-table = -2,00324. Therefore, partially, professionalism had a positive and significant effect while time budget pressure and audit complexity had a negative and significant effect on audit quality at public accounting firm in Medan. The result of coefficient of determination analysis was 0.374, which means that variation of audit quality variables can be explained by variation of professional variables, time budget pressure, and complexity of audit up to 37.4% and the remaining 62.6% can be explained by other independent variables.